The Imiquimod Induced Psoriatic Animal “Model: Scientific Implications - 반츠라크치; 함정엽; 김진철 (2019)
Psoriasis is a chronic inflammatory auto-immune disease, which causes serious skin lesions, acanthosis and parakeratosis, leaving a long-lasting detrimental influence on our appearances and life quality. Though a huge scientific information regarding psoriasis-related mechanism and pathological analysis is getting accumulated over the last decades in the price of valuable experiments and efforts of many experts. However, an absence of reliable mouse model has been a major obstacle to further advances in psoriasis research. Recently, a topical application of imiquimod (IMQ), classical Toll-like Receptor (TLR)-7 agonist, has provided a strong foundation of psoriasis study on the animal model as it stimulates cutaneous phenotype similar to human psoriasis in the mouse. IMQ-mediated skin inflammation often exhibits slight divergences on human psoriasis and extensive investigations to yield more suitable psoriatic model are taking place. In this review, we summarized the recent novel breakthroughs on improving existing IMQ model and discovering a new model of psoriasis and discussed their importance on psoriasis research.